Pengaruh Tingkat Kecemasan Terhadap Career Interest Pada Siswa Dan Siswi Sekolah Menengah Atas - Yuliza, Rahma; Nursa’adah, Nursa’adah; Iskandar, Iskandar (Jurusan Keperawatan, Poltekkes Kemenkes Palembang, 2025)
Background: Career interest refers to an individual's desire and motivation to pursue a particular career. Those who are interested in pursuing a career are typically individuals who wish to make life decisions aligned with their personality type. However, challenges such as anxiety can arise when determining future career paths. Career-related anxiety is a form of realistic anxiety, associated with feelings of uncertainty and potential negative impacts on future life. Objective: This study aims to examine the influence of anxiety levels on career interest. Method: The research method used is descriptive correlational with a cross-sectional study design. The population consists of all 12th-grade students, totaling 279 individuals. The sampling technique used is purposive sampling, with the Slovin formula applied to obtain a sample of 74 students. Data collection instruments included a questionnaire sheet. Results: The study found that the majority of students had low career interest (45 respondents or 60.8%) and high levels of anxiety (41 respondents or 55.4%). The statistical analysis revealed a significant influence of anxiety levels on career interest, with a p-value = 0.000 (p < 0.05). Conclusion: This study concludes that anxiety levels significantly affect career interest among students at SMA Negeri 8 Banda Aceh. It is hoped that students can reduce their anxiety levels to foster stronger career interest in the future.